'Bats below the bridge': is a potentially treatable neurovascular disorder being underdiagnosed in accident and emergency departments?. Issue 2 (June 1994) - Hulbert, D; Gabe, S; Potts, D; Ball, J A; Touquet, R
Abstract : Basilar artery thrombosis (BATS) is a progressive disorder which may present with fluctuating neurological signs of varying degrees of severity. Unless the diagnosis is considered, the confused young patient may be thought to be under the influence of drugs or to be psychologically ill, and indeed the Munchausen syndrome may be considered. The more elderly patient may be diagnosed simply as having had a cerebrovascular accident. This paper presents the cases of three patients admitted through the accident and emergency (A&E) department of St Mary's Hospital, London with basilar artery thrombosis during a 6-month period. All these patients demonstrated the classic triad for this syndrome of: (1) long tract neurological signs, (2) impaired conscious level, and (3) complex ocular signs. The concern is that, for patients with more subtle signs, a diagnosis of BATS may not be considered, and a neurological opinion may be thus delayed and no treatment with anticoagulants or thrombolytic agents would be given. Two of the three patients were treated with anticoagulants and improved, while in the third patients anticoagulation was judged inappropriate and the patients died from progression of the disease with respiratory complications.